Soberania e segurança alimentar e nutricional em assentamentos rurais: um estudo de caso sobre o acesso aos alimentos no sudoeste do Paraná - Fraga, Ligia Kochhan de (2024)
The development of studies on agrarian issues and FNSI (Food and Nutrition Security and Insecurity) in rural areas can play a fundamental role in promoting a critical analysis of the social and economic dynamics that perpetuate inequality and injustice in rural settings. Through an interdisciplinary approach, this research is justified by the need for a deeper understanding of the challenges faced by rural communities in order to contribute to the formulation of public policies and sustainable development strategies. The research aimed to analyze the dynamics of production and consumption, as well as strategies for access to food adopted by farming families, from the perspective of FNS (Food and Nutrition Security), in the rural settlement Anjo da Guarda I, Mangueirinha, Paraná. The study was a descriptive case study with a quantitative/qualitative approach, employing a concurrent triangulation strategy, and it was submitted to and approved by the research ethics committee involving human subjects at UTFPR. Thirty families participated in the study, which were visited between May 2023 and February 2024. The data analysis was organized into three dimensions, which were subsequently triangulated and contrasted: the sociodemographic profile of the participants; food and nutrition security and levels of food insecurity among the families; and food production and consumption. The results revealed that more than half of these families (56.6%) face some degree of FNSI, while 43.3% can be classified as food secure. No cases of severe food insecurity were identified in the study area. The lack of access to implementation credits, especially for housing, was one of the limiting factors for FNS in the settlement in question. It was also found that there is an interaction between marketization, through grain specialization for commercialization, and an increase in the prevalence of FNSI. The research pointed to the urgency of considering a complementary scale to the EBIA (Brazilian Food Insecurity Scale) to assess food sovereignty, since the term has already been incorporated into FNS. For instance, indicators such as food production methods and consumption of ultra-processed foods could be used. The study also allowed the identification of the importance of community reciprocity relationships from the perspective of FNS, a specific strategy of rural areas that not only strengthens community ties but also provides access to a greater variety of food.